Cogito, Machina, Sum: The Era of AI-Crafted Digital Identities - Aiswaria Samyuktha S; Mathangi V (Tattva Journal of Philosophy, 2024)
AI personalization is used in variety of areas offering improved user experience. The integration of AI in entertainment leads to the very commodification and mere reproduction of existing works. The nature of creativity and human-AI collaboration is complex and a multifaceted area of exploration. While culture influences the evolution of AI, AI likewise impacts culture in various ways. Generative AI in the recent years have seen remarkable growth. With its application in the creative field there are debates and repudiation over the creative works by AI. Consequently, there is a need for redefining creativity in the era of AI especially with the emergence of promptology, synthography etc., Derrida’s différance highlights the instability of meaning. And Artificial Intelligence through algorithms interpret and generate text and images, this shows that the digital content is never fixed, and it is continually deferred and evolving. This also leads to the discussion on authenticity. Thus, this paper aims to critically examine the boundaries, authenticity and power dynamics in digital identities in the AI driven era. KEYWORDS: Generative AI, Digital Self, Art, HMI Top of Form